The decision usefulness of six reporting capitals among non-financial integrated reporting participating firms - Wong, Yih Jenq (2019)
Integrated reporting framework has been introduced since year 2013, and its current literature streams focuses on normative approaches rather than focuses on integrated reporting’s practice and its applications. Therefore, this study contributes to the growing literature on integrated reporting and discusses broadly on the relevance of its capitals, which includes financial capital, manufactured capital, human capital, intellectual capital, natured capital, and social and relational capital. This study uses Ohlson model, which is the multivariate regression, to address the effectiveness of six reporting capitals to firm performance. Furthermore, it uses mean difference test to identify whether the quality of reporting disclosure has been improved from traditional reporting to integrated reporting among listed integrated reporting participating firms. Specifically, this study presents that some of the capital indications are predicted correctly and significantly. The inclusion of financial capital, human capital and intellectual capital significantly enhances firm value. The presentation of these three capitals provides a better and clearer picture for firm performance. However, the results for manufactured capital, natured capital, and social and relational capital are insignificant and indicate that they are unlikely to enhance firm value. This study also concludes that integrated reporting presents better disclosure quality of reporting compared to traditional reporting format.